Measurement of critical stress intensity factor in C/C-SiC composites under dynamic and static loading conditions - Srivastava V.K.; Maile K. (My University, 2025)
In the present investigations split Hopkinson pressure bar (SHPB) and four point bending tests were performed to determine the stress intensity factor of oxidised (1600 °C for 15 min) and unoxidised chevron notched carbon-carbon silicon carbide (C/C-SiC) composite specimens. The split Hopkinson input bar was used to load the pre-cracked specimen with the reflected tensile pulse from the end of the specimen, whereas, four point bending test was used to load the pre-cracked specimen with gradual transfer of bending force to the variation of loading rate. The morphology of the fractured areas was examined by the scanning electron microscope analysis. These results clearly indicate that the stress intensity factor of C/C-SiC composite was very much effected by the loading rates and conditioning of materials. © 2004 Published by Elsevier Ltd.